Prevalence of COPD and its association with socioeconomic status in China: Findings from China Chronic Disease Risk Factor Surveillance 2007 - Jiang Yong; Li Yichong; Zhang Mei; Yin Peng; Zhao Wenhua (BMC, 2011)
Abstract Background Socioeconomic status is likely an independent risk factor for Chronic Obstructive Pulmonary Disease (COPD), but little research has been done in China to study this association in a nationwide sample. Methods We used data from the 2007 China Chronic Disease Risk Factor Surveillance of 49,363 Chinese men and women aged 15-69 years to examine the association between the prevalence of self-reported physician diagnosed COPD and socioeconomic status defined by both educational level and annual household income. Multivariable logistic regression modelling was performed with adjustement for potential confounders. Results Both low educational attainment and low household income were independently associated with higher risk of physician-diagnosed COPD. Compared to subjects with high educational level, subjects with low educational level had a significantly increased risk of COPD (OR 1.67, 95%CI 1.32-2.13, p for trend< 0.001 for urban, OR 1.76, 95%CI 1.34-2.30, p for trend < 0.001 for rural) after adjusting for age, sex, smoking status, passive smoking and geographic regions. Similarly increased risk was observed for household income and COPD in urban (OR 1.64, 95%CI 1.28-2.09, P for trend< 0.001) but not rural areas. Among never smokers, low educational level and household income were still associated with a significant higher prevalence of COPD (OR 1.77, 95%CI 1.40-2.25, OR 1.31, 95%CI 1.05-1.62). Removal of those with asthma diagnosis did not alter the observed associations. Conclusions Socioeconomic status is a risk factor for self-reported physician-diagnosed COPD independently of current or passive smoking. Prospective studies are needed in China to better understand the association between socioeconomic status and COPD.